Getting your message right : communicating effectively with employees - Davis, Alison (Alison Bonnie), 1957- (FT Press Delivers elements., 2011)
This Element is an excerpt from The Definitive Guide to HR Communication: Engaging Employees in Benefits, Pay, and Performance (9780137061433) by Alison Davis and Jane Shannon. Available in print and digital formats. Employee communication solutions that work: three easy approaches to successfully framing virtually any message. You've just presented to senior management. Your PowerPoint deck was appropriately detailed: 44 slides explaining why the program is needed, how you designed it, and what it contains. Your hard work paid off: Management gave you the go-ahead. Now it's time to communicate with employees. First step: close that PowerPoint and take out a blank sheet of paper...